Demonstration of inscription and ablation of phase masks for the production of 1st, 2nd, and 3rd order FBG gratings using a femtosecond laser - Smith, Graham N.; Kalli, Kyriacos; Bennion, Ian; Sugden, Kate (My University, 2009)
We present to the best of our knowledge the first example of femtosecond laser inscription/ablation of phase/amplitude masks for the demonstrated purpose of inscribing Bragg gratings in optical fibers. We show that the utilization of a femtosecond laser for the mask production allows for great flexibility in controlling the mask period. The masks are used to produce 1st, 2nd and 3rd order fiber Bragg gratings (FBGs) in SMF-28. The work demonstrates the proof of concept and flexibility for the use of femtosecond lasers for the rapid prototyping of complex and reproducible mask structures. Our inscription studies are augmented by considerations of three-beam interference effects that occur as a result of the strong zeroth-order component that is present in addition to higher-order diffraction components.